A review of moxidectin vs. other macrocyclic lactones for prevention of heartworm disease in dogs with an appraisal of two commercial formulations - Mwacalimba, Kennedy; Sheehy, Jenifer; Adolph, Christopher; Savadelis, Molly; Kryda, Kristina; Poulsen Nautrup, Barbara (Frontiers in Veterinary Science, 2024)
Macrocyclic lactones (MLs) are the only drug class currently licensed for heartworm disease prophylaxis. Macrocyclic lactones kill third-and fourth-stage larvae of Dirofilaria immitis, thus preventing the development of adult worms in dogs, which are responsible for heartworm disease, a potentially life-threatening condition. Despite considerable overlap in terms of endectocide spectrum, several important differences distinguish moxidectin from other MLs. Moxidectin has beneficial pharmacokinetic characteristics, such as a longer half-life and greater tissue distribution compared to ivermectin. Additionally, moxidectin has a greater margin of safety compared to ivermectin in dogs with ABCB1 (previously MDR1) gene-defect, which is commonly recognized in collies and other breeds. Multiple laboratory studies have shown that moxidectin is more effective than other commonly used heartworm preventives against resistant strains of D. immitis. This improved efficacy benefits individual dogs and helps reduce the risk of spreading resistant strains within the community. Despite the presence of proven resistant strains in the US, non-compliance with preventive measures remains a major factor contributing to the diagnosis of heartworm disease in dogs. In retrospective analyses, the oral moxidectin combination product Simparica Trio ® (sarolaner, moxidectin and pyrantel) was associated with increased compliance, resulting in more time of protection compared to dogs receiving flea/tick and heartworm preventive products separately.Compliance with the extended-release moxidectin injectables ProHeart 6 and ProHeart 12 was higher than with monthly heartworm preventives, as they provide 6 months or a full year of protection with one single injection, respectively, and revenues remain in the veterinary clinics as injectable moxidectin cannot be sourced through online retailers.